What can the Māori-led COVID Roadblocks tell us about a Bicultural Future Legal System in Aotearoa New Zealand? - Fitzmaurice, Luke (Legalities, 2021)
Keywords: covid checkpoints; law; rangatiratanga; sovereignty; tikanga | indigenous law

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

The treaty claims settlement process in New Zealand and its impact on Māori - Mutu, Margaret (2019)
This article considers research conducted on the impact of the Crown’s treaty claims settlement policy on Māori in New Zealand. It provides a brief background to the Treaty of Waitangi and the subsequent British colonisation process that relied on the Doctrine of Discovery in breach of the treaty. It outlines how colonisation dispossessed Māori of 95 percent of their lands and resources, usurped Māori power and authority and left them in a state of poverty, deprivation and marginalisation while procuring considerable wealth, prosperity and privilege for British settlers. The work of the Waitangi Tribunal, the commission of inquiry set up to investigate those breaches, is considered, as is the Crown’s reaction to the 1987 Lands case in developing its treaty claims settlement policy. The Crown unilaterally imposed the policy despite vehement opposition from Māori. Since 1992, it has legislated more than seventy ‘settlements’. The research shows that overall, the process has traumatised claimants, divided their communities, and returned on average less than one percent of their stolen lands. Proposals for constitutional transformation have drawn widespread support from Māori as a solution to British colonisation. United Nations treaty-monitoring bodies have recommended that the government discuss this with Māori
Keywords: colonisation; constitutional transformation; crown policy; law; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Does the crown minerals act undermine partnership with Maori? - Billington, Carl (Public sector (Wellington), 2022)
The Crown Minerals Act 1991 (CMA) was introduced "to promote prospecting for, exploration for, and mining of Crown owned minerals for the benefit of New Zealand". A series of fundamental questions has emerged as to whether the Act undermines the ability of the Crown and tangata whenua, anchored in Te Tiriti o Waitangi, to operate in a true sense of partnership. Carl Billington takes a closer look.
Keywords: crown lands; crown policy; land tenure; law; legislation; mines and mineral resources; mining law; tiriti o waitangi/treaty of waitangi; treaty obligations